2015
DOI: 10.1117/12.2183777
|View full text |Cite
|
Sign up to set email alerts
|

Endovenous laser therapy for occlusion of incompetent saphenous veins using 1940nm

Abstract: Objective:Several studies indicate that ELT using wavelengths of high water absorption showed advantages compared to conventional ELT. Thulium-Lasers emit nearby the local absorption maximum of water at 1940nm. In this clinical study the effectiveness, safety and the feasibility of 1940nm-ELT is proven. Materials and Method:A single centric, prospective observational study was performed. 1940nm-laserenergy was applied using radial emitting fibres with continuous pullback (1mm/s). Treatment was performed under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…According to previous literatures, the required energy for good outcomes is about 80-100 LEED (J/cm) with the 1,470nm EVLA (11,13,14). And to date, a few studies have investigated EVLA using the 1,940-nm laser, and this treatment has generally produced good outcomes, even with energy < 50 LEED (J/cm) (19)(20)(21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…According to previous literatures, the required energy for good outcomes is about 80-100 LEED (J/cm) with the 1,470nm EVLA (11,13,14). And to date, a few studies have investigated EVLA using the 1,940-nm laser, and this treatment has generally produced good outcomes, even with energy < 50 LEED (J/cm) (19)(20)(21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22] In addition to the well-established diode laser with emission wavelength of 1470nm (active medium: InGaAsP), new semiconductor diode-based lasers with wavelengths of interest have been emerging, including emission wavelengths centered on 1908nm, 1920nm, and 1940nm (active medium: AlGaIn). 8,23 The practical advantages of these wavelengths are also because of the high degree of absorption of laser light by the interstitial water in the vein walls, which can be illustrated by their respective absorption coefficients (μ A water ) for this chromophore (Table 7). 24 It can be considered that delivering laser light to the vein wall via a radial fiber at a λ in the region of 1940nm is an incremental development over the current state-of-the-art technique for laser endovenous thermoablation, which is the 1470nm laser with irradiation via a radial fiber.…”
Section: Discussionmentioning
confidence: 99%
“…Many different wavelengths and different types of optical fibers have been tested in attempts to achieve this objective. [1][2][3][4][5][6][7][8] Several authors have demonstrated that all of the wavelengths employed to treat varicose veins are equally capable of producing the desired anatomic results. The fundamental differences between different wavelengths are related to occurrence of adverse events.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] However, there are few studies on the effective power or LEED at a longer wavelength of 1940 nm, and all have focused on radial fibers. 6,[14][15][16] In addition, no studies have specifically investigated the Asian population.…”
Section: Introductionmentioning
confidence: 99%